Distortion product oto-acoustic emission spectra and speech identification scores in individuals with auditory neuropathy spectrum disorder - Avilala, Vijay Kumar Yadav; Prabhu, Prashanth; Barman, Animesh (Journal of All India Institute of Speech and Hearing, 2013)
The objective of the study was to compare the specific patterns in distortion product oto-acoustic emissions (DPOAE) spectra and its relationship with speech identification scores in individuals with auditory neuropathy spectrum disorder (ANSD). The DPOAE spectra and speech identification scores of 15 normal hearing and 30 individuals diagnosed as having auditory neuropathy spectrum disorder were studied and compared. DP-gram Spectra was also analyzed in patients with auditory neuropathy spectrum disorder who were further divided into good and poor performers based on their speech identification scores. The results indicated that the mean DPOAE amplitudes across frequencies obtained for good and poor performers of ANSD suggests that the irregularity in DPOAE spectra is more for poor performers than the good performers. The number of notches, depth of notches and the width of the notches are more for poor performers with ANSD. In conclusion, the findings of the present study suggest that individuals with auditory neuropathy spectrum disorder exhibit subtle abnormality in the peripheral auditory system.